The SAFE Experimental Research on the Frequency Dependence of Shear Wall Seismic Design Margins. Issue 1 (2nd January 2016) - Labbé, Pierre; Pegon, Pierre; Molina, Javier; Gallois, Christian; Chauvel, Danièle
Abstract : The SAFE experimental programme consists of a series of 10 specimens of shear walls, with different reinforcement ratios, tested until their ultimate capacity under seismic input motion by the pseudo dynamic method. A unique input signal is used, calibrated for controlling the seismic demand. Its input central frequency is selected so that for some specimens it is lower than their eignenfrequency, while for other ones it is the opposite. In conclusion there is clear experimental evidence that design margins are much larger in the second case (input central frequency larger than structure eignenfrequency) than in the first one.